Perancangan cup set matcha stoneware bergaya Japandi - Firna Fauziah Subihaki; Ghia Tri Jayanti; Handayani Madania Insani (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2026)
The trend of matcha consumption continues to experience growing interest throughout Indonesia in 2025. This phenomenon presents an opportunity for the ceramics industry regarding the need for matcha consumption serving ware. This research aims to design a cup set using stoneware material, employing a User-Centered Design approach that focuses on user needs and preferences. To achieve this objective, the research begins with an industry analysis at a local pottery studio called Biomorphic, which uses stoneware material in its products. The research was conducted by identifying production potential and capacity using SWOT analysis tools. Subsequently, a market validation stage was carried out using Google Trends, and user needs analysis with a case study approach at a Japandi-style café as a reference for taste and presentation preferences. Design decision-making utilized visual scale analysis tools and product positioning. The research results comprise a cup set prototype using stoneware material with Japandi aesthetics in accordance with user needs. Validation was conducted through field testing, which demonstrated that the design aligns with Japandi interior aesthetics and fulfills the serving function for cafés.Published Date: 2026-07-26